Linkage to care following community‐based mobile HIV testing compared with clinic‐based testing in Umlazi Township, Durban, South Africa1. Issue 6 (19th November 2013) - Bassett, IV; Regan, S; Luthuli, P; Mbonambi, H; Bearnot, B; Pendleton, A; Robine, M; Mukuvisi, D; Thulare, H; Walensky, RP; Freedberg, KA; Losina, E; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess HIV prevalence, disease stage and linkage to HIV care following diagnosis at a mobile HIV testing unit, compared with results for clinic‐based testing, in a Durban township. Methods This was a prospective cohort study. We enrolled adults presenting for HIV testing at a community‐based mobile testing unit (mobile testers) and at an HIV clinic (clinic testers) serving the same area. Testers diagnosed with HIV infection, regardless of testing site, were offered immediate CD4 testing and instructed to retrieve results at the clinic. We assessed rates of linkage to care, defined as CD4 result retrieval within 90 days of HIV diagnosis and/or completion of antiretroviral therapy (ART) literacy training, for mobile vs. clinic testers. Results From July to November 2011, 6957 subjects were HIV tested (4703 mobile and 2254 clinic); 55% were female. Mobile testers had a lower HIV prevalence than clinic testers (10% vs. 36%, respectively), were younger (median 23 vs. 27 years, respectively) and were more likely to live >5 km or >30 min from the clinic (64% vs. 40%, respectively; all P < 0.001). Mobile testers were less likely to undergo CD4 testing (33% vs. 83%, respectively) but more likely to have higher CD4 counts [median (interquartile range) 416 (287–587) cells/μL vs. 285 (136–482) cells/μL, respectively] than clinic testers (both P < 0.001). Of those who tested HIV positive, 10% of mobile testers linked to care, vs. 72% of clinic testers (P < 0.001). Conclusions Mobile HIV testing reaches people who are younger, who are more geographically remote, and who have earlier disease compared with clinic‐based testing. Fewer mobile testers underwent CD4 testing and linked to HIV care. Enhancing linkage efforts may improve the impact of mobile testing for those with early HIV disease.